Knowledge regarding the population served by Social Work interns - Sampaio, Simone Sobral; de Oliveira, Robson (Argumentum, 2020)
This article presents Supervised Internships in Social Work as an important means for learning the dynamics of professional practice. Within the scope of the research, this article highlights a gap in discussions around the topic, namely, knowledge regarding the population that seeks out Social Service assistance. The text presents the Curricular Guidelines, vocational training objectives, and the possibilities offered by knowledge of the population served by Social Workers. It concludes that knowing the served population is a strategic element in designing policy that then determines the social direction of the profession, especially with regards to defining strategies that enable the establishment of a relationship contrary to institutionalization and which reinforces bonds in social workers’ professional practice.Keywords: Supervised Internship. Professional Practice. Served Population.